Exploring the acceptance of ChatGPT in higher education: a comprehensive quantitative study of university students and faculty - Kaya, Mehmet Haldun; Adıgüzel, Tufan (Frontiers in Education, 2025)
The study explores the acceptance and use of ChatGPT in higher education, focusing on university students and faculty members. The research aims to identify the factors that influence the behavioral intention to use ChatGPT, utilizing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) as the theoretical framework. Key constructs such as performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit were examined for their impact on the acceptance of ChatGPT. Data were collected through a survey of 378 participants, including 346 students and 32 faculty members, from various faculties at a university in Eastern Europe. The findings reveal that effort expectancy and performance expectancy were the most significant predictors of behavioral intention to use ChatGPT. Faculty members demonstrated a higher intention to use ChatGPT compared to students, likely due to their greater experience with technology. Hedonic motivation also played an important role in both groups, indicating that enjoyment contributed to the acceptance of the tool. The study concludes that ChatGPT holds great potential for enhancing education, but its habitual use is not yet widespread. The results suggest that universities should focus on improving institutional support and training to facilitate broader acceptance of ChatGPT among students and faculty.